A study of cytotoxicity and proliferation of Cosmos caudatus Kunth leaf extract in human gingival fibroblast culture - Zhafira Nur Shabrina; Ni Putu Mira Sumarta; Coen Pramono (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: Post-extraction dental sockets clinically resolve within a period of 3-4 weeks. However, complete healing and bundling of gingival fibers may require several months. Medication is therefore required to accelerate the healing process. Cosmos caudatus (C. caudatus), a local plant with antioxidant properties and high calcium content, has the potential to promote wound healing while also reportedly capable of strengthening bone. Previous studies have demonstrated the effectiveness of C. caudatus as an alternative treatment for post-menopausal osteoporosis by investigating the dynamic and cellular parameters of bone histomorphometry. Purpose: The study aimed to examine the citotoxicity and proliferation of human gingival fibroblast cells culture after the application of C. caudatus extract. Methods: Cultures of human gingival fibroblast cells with 5x104 cell density were divided into two groups and placed in a 30-well culture dish. The control group contained human gingival fibroblast cell culture without extract, while the experimental group consisted of human gingival fibroblast cells culture with extract. The concentrations of extract were 1200 μg/ml, 600 μg/ml, 300 μg/ml, 150 μg/ml, and 75 μg/ml. A toxicity test was conducted and the optimum concentration evaluated using an MTT assay, while fibroblast numbers on were calculated days 1 and 2 by means of a hemocytometer. Research data was analyzed using a one-way ANOVA test. Results: No toxicity was found. The optimum concentration was 600 μg/ml and fibroblast proliferation was significantly higher in the experimental group compared to the control group, p=0.002 (P<0.05). Conclusion: C. caudatus leaf extract is non-toxic and increases the proliferation of human gingival fibroblast culture at an optimum concentration of 600 μg/ml.